Research on the Reform of Authorized Capital System in Chinese Stock Companies: Against the Background of the Implementation of the New Company Law - Wu, Yanlin (Journal of Theory and Practice of Social Science, 2024)
With the rapid development of the Chinese economy and the continuous improvement of the market economy system, joint-stock companies, as an important form of economic organization, have gradually become the main force of economic development. In order to adapt to the new development trend, China has successively introduced a series of laws and regulations, attempting to reform and improve the authorized capital system, enhance corporate governance, protect investor rights, and promote the healthy development of the market economy. This article analyzes the current situation and problems of the statutory capital system of Chinese joint-stock companies, and based on this, analyzes the reform effects of the new Company Law on the authorized capital system of joint-stock companies. It also explores the transformation path of the authorized capital system of Chinese joint-stock companies after the implementation of the new Company Law, providing reference opinions for the development of joint-stock companies and the optimization of the efficiency of capital system reform.